ANALISIS MUTU IMPLEMENTASI PENDIDIKAN GRATIS DI JABODETABEK - Latip, Asep Ediana; Wafiqni, Nafia (JMIE (Journal of Madrasah Ibtidaiyah Education), 2017)
This study aimed to analyze the quality of the implementation of free education at the level of free education in Jabodetabek. Subjects were implementing elements of the free education that teachers and principals in the area of Jakarta, Bogor, Depok, Tangerang and Bekasi. This research is non-experimental research because no manipulation of study variables. The type of research is a survey method. This research data collection techniques are questionnaires and observation techniques. Questionnaires and observation selected in this study, because of the variables to be measured is certain, that the quality of the implementation of free education at the primary level. This technique is also an effective technique for measuring the purpose of this study of the respondents are already established. The research result shows that the implementation of free education in Jabodetabek meet the quality standards of education good views of inputs, processes, outputs, and outcomes of education. Judging from the quality standard based education accreditation, quality free education in Jabodetabek meet the quality standards of education with the acquisition value of A. Model implementation of free education of the funding envisaged in three models of education, namely the liberation of all kinds of levies by schools to parents, Liberation operational cost of education to parents, except for expenses for personal needs such as school uniforms and operational financing of education imposed on BOS (School Operational Cost). Impact of free education based on the quality of the inputs, processes, outputs, and outcomes, as well as quality accreditation are also models of implementation of free education for the elderly, the implementation of free education in Jabodetabek with quality standards do not have the participation of parents is optimal, had the satisfaction of graduates, and assisted from the financing of education free of charge. For teachers based on the acquisition of data about the quality of free education, teachers meet standards with optimal learning process.